Nutritive Value of Desert Truffles Species of Genera Terfezia and Picoa (Ascomycetes) from Arid and Semiarid Regions of Eastern Turkey - Akyuz, Mehmet; Kirbag, Sevda (Begell House Inc, 2018)
Terfezia and Picoa species contained 63-94 kcal energy, 76.93-83.81 g moisture, 0.78-1.52 g ash, 2.19-4.69 g protein, 2.14-9.48 g carbohydrate, 2.54-11.23 g dietary fiber, and 0.96-3.40 g fat per 100 g wet weight. We determined that Terfezia species contain more vitamin E and malondialdehyde than do Picoa species, but the amounts of vitamin A, vitamin C, and beta-carotene may vary. Picoa species contain less palmitic and stearic acids but more oleic acid than do Terfezia species. Amino acid analyses revealed that glutamic and aspartic acid were the most abundant. We also noted that Picoa species have larger amounts of glucose and fructose than do Terfezia species. In addition, the elements these mushrooms contain can vary, but they are found at nutritious levels and are below toxic levels.
Keywords: amino acids; arid-semiarid truffles; edible and medicinal mushrooms; element; fatty acid; Picoa; sugar; Tetfezia; vitamin